Overexpression of E-cadherin protein in metastatic breast cancer cells in bone - Baisakhi Saha (2018)
Aim: The aim of the present study was to evaluate E-cadherin, whose expression remains poorly understood in the intercellular adhesion of metastatic breast cancer cells in bone, the most prevalent site for metastatic growth. Materials and Methods: An immunohistochemical staining method was used for the localization of E-cadherin protein in tissue biopsy specimens of normal breast (n = 9) and well- (n = 8), moderately (n = 8) or poorly (n = 14) differentiated invasive primary breast cancer and metastatic breast cancer in bone (n = 17). The expression patterns of E-cadherin were classified as homogeneous (most cells exhibiting positivity), heterogeneous (a few scattered patches of cells with positivity) or negative (cells with undetectable positivity). Results: Normal breast epithelial cells showed homogeneous overexpression of E-cadherin in all cases. A progressive and statistically significant reduction of E-cadherin expression was detected in the histologically well- to moderately to poorly differentiated breast cancer cells (p < 0.001). The clumps of invasive primary breast cancer cells in CD-31-positive blood vessels exhibited E-cadherin expression. Moreover, as compared to the poorly differentiated breast cancer cells, a significantly increased frequency of the metastatic breast cancer cells in bone exhibited homogeneous expression of E-cadherin in 15 out of 17 and heterogeneous expression in the remaining 2 cases (McNemar Exact p < 0.001). This is the first demonstration of membranous overexpression of E-cadherin on metastatic breast cancer cells in bone; the high frequency of its expression may have a role in the intercellular adhesion of metastatic cells in bone.